Pengembangan Media Permainan Truth or Dare pada Pembelajaran Pendidikan Pancasila - Rosyada, Amrina; Hamdan, Hamdan; Krisnawati, Yuni (JOEAI (Journal of Education and Instruction), 2025)
This study aims to develop a valid and practical Truth or Dare game for Pancasila Education learning in the fifth grade at SD Negeri 37 Lubuklinggau. The research method used R&D with the ADDIE model. The results showed that the developed product was "Valid" with a score of 0.92, categorized as very high. The practicality assessment sheet analysis by educators and students met the "Practical" criteria, earning an 83.52% score and being categorized as very practical. Based on the results, it can be concluded that the Truth or Dare game for Pancasila Education learning in fifth grade at SD Negeri 37 Lubuklinggau is proven valid and practical, making it suitable for use in Pancasila Education learning in fifth grade at SD Negeri 37 Lubuklinggau.   Keywords: Truth or Dare Game, Pancasila Education, Development, Elementary School